PENERAPAN PEMBELAJARAN KOOPERATIF TEKNIK KELILING KELOMPOK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X SMA NEGERI 10 PEKANBARU - Farita Sukma; Elva Yasmi Amran; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research about application of cooperative learning techniques roving group has been done to improve student’s achievement on the topic of chemical bonds at 10th of SMAN 10 Pekanbaru on 02 October- 06 November 2013. This research is experimental research based on pretest-posttest design. The sample consisted of two classes, X4 class as experiment class and X3 class as control class that randomly selected after testing homogeneity. Application of cooperative learning techniques roving group applied in experiment class. Analysis of data used t-test. Results of data processing obtained tcount>ttable (3,678> 1,67). It means that the application of cooperative learning techniques roving group can improve student’s achievementon the topic of chemical bonds at 10th of SMAN 10 Pekanbaru. The improvement of student’s achievement in experiment class is 16,796%.Keywords: Cooperative Learning Techniques Roving Group, Student Achievement, Chemical Bonds